The Effect of Sansevieria Extract on Indoor Carbon Monoxide from Cigarette Smoke - Rizky Rahadian Wicaksono; Muhammad Hanif; Marsha Savira Agatha Putri; Eka Sarofah Ningsih; Carri Noer Yanik (Gema Lingkungan Kesehatan, 2026)
Air quality degradation can occur through changes in physical or chemical properties. Biodiversity in Indonesia can be a solution to the increasingly concerning air pollution problem. There are many types of plants that have the potential to absorb cigarette smoke air pollution, including sansevieria. Sansevieria plants can reduce both indoor and outdoor air pollution, particularly CO from cigarette smoke. Furthermore, NASA research has found evidence that this plant naturally absorbs toxic materials such as carbon dioxide, benzene, and formaldehyde. Purpose The purpose of this study was to determine the effectiveness of Sansevieria plant extract in absorbing cigarette smoke pollution, specifically CO gas. The study compared indoor CO levels from cigarette smoke with and without snake plant extract, using three replicates (or trials). Sensitivity tests showed that 1.5 grams of snake plant ethanol extract reduced carbon monoxide levels by 89.5 ppm within 15 minutes per cigarette. So it can be concluded that the extracts of the Sansevieria masoniana and trifasciata laurentii plants are useful as a solution to air pollution.